Elementos para uma crítica à ideologia do atraso brasileiro - Monetti, Fabiano (2011)
The object of this dissertation was focused on the analysis of elements of the perception of Brazilian backwardness as an ideology in close relation with the modernization process in our country. Aspects of this perception, taken in its impressionistic manifestations, often do not relate only to the objective conditions of reality, but also to an even pre-reflective willingness, that reveals, in turn, a sense of inferiority. Thus, here it was tried to deepen the analysis of this ideological component to the extent that it is somewhat reproduced in the social and political thought produced by interpreters of Brazil. Some reflections of the sociologist Jessé de Souza on the Gilberto Freyre s works Casa-grande e senzala and Sobrados e mucambos were taken as an axis, giving prominence to the notion of "Brazilian cultural uniqueness", among others. In these arguments, it was attempted to establish points of contact and divergence with Raízes do Brasil by Sérgio Buarque de Holanda